Exterior Site Occupancy Infers Chloride-Induced Proton Gating in a Prokaryotic Homolog of the ClC Chloride Channel - Bostick, David L. (Biophysical Society, 2004)
The ClC family of anion channels mediates the efficient, selective permeation of Cl(−) across the biological membranes of living cells under the driving force of an electrochemical gradient. In some eukaryotes, these channels are known to exhibit a unique gating mechanism, which appears to be triggered by the permeant Cl(−) anion. We infer details of this gating mechanism by studying the free energetics of Cl(−) occupancy in the pore of a prokaryotic ClC homolog. These free energetics were gleaned from 30 ns of molecular dynamics simulation on an ∼133,000-atom system consisting of a hydrated membrane embedded StClC transporter. The binding sites for Cl(−) in the transporter were determined for the cases where the putative gating residue, Glu(148), was protonated and unprotonated. When the glutamate gate is protonated, Cl(−) favorably occupies an exterior site, S(ext), to form a queue of anions in the pore. However, when the glutamate gate is unprotonated, Cl(−) cannot occupy this site nor, consequently, pass through the pore. An additional, previously undetected, site was found in the pore near the outer membrane that exists regardless of the protonation state of Glu(148). Although this suggests that, for the prokaryotic homolog, protonation of Glu(148) may be the first step in transporting Cl(−) at the expense of H(+) transport in the opposite direction, an evolutionary argument might suggest that Cl(−) opens the ClC gate in eukaryotic channels by inducing the conserved glutamate's protonation. During an additional 20 ns free dynamics simulation, the newly discovered outermost site, S(out), and the innermost site, S(int), were seen to allow spontaneous exchange of Cl(−) ions with the bulk electrolyte while under depolarization conditions.